Decision to Delivery Time and Its Predictors Among Mothers Who Underwent Emergency Cesarean Delivery at Selected Hospitals of Northwest Ethiopia, 2023: Prospective Cohort Study [Letter] - Ahmad M (Dove Medical Press, 2024)
Mardiana Ahmad Department Master of Midwifery, Postgraduate School, Hasanuddin University, Makassar, IndonesiaCorrespondence: Mardiana Ahmad, Department Master of Midwifery, Postgraduate School, Hasanuddin University, Makassar, Indonesia, Email mardianaahmad@pasca.unhas.ac.id